Genetic control of nitrogen stress tolerance in winter wheat - Laperche A.; Brancourt-Hulmel M.; Hanocq E.; Ney B.; Devienne-Barret F.; Le Gouis J. (Cereal science and technology for feeding ten billion people: genomics era and beyond, 2008)
Breeding wheat adapted to low nitrogen (N) input will be favoured by environmental and economical concerns. Thus, it is worth studying the genetic control of wheat N stress tolerance. We investigated a population of 220 di-haploid (DH) lines derived from the cross between a N stress tolerant and a sensitive cultivar. QTL were detected for sensitivity to N stress and for traits involved in plant functioning under N-limited conditions. The population was evaluated for grain yield and its components in multi-environment field trials under low and high N levels as well as and in growth chamber under N-limited condition. N stress sensitivity was estimated as the slope of a factorial regression where grain yield was regressed on the nitrogen nutrition index (NNI) of cv. 'Récital' measured in each trial. Plant functioning under N-limited conditions was evaluated in growth chamber using a conceptual crop model and a root system characterization. Seven QTL were detected for N stress sensitivity and fourteen were detected for plant functioning. A majority of QTL was detected in the vicinity of the dwarfing gene Rht-B1. Results indicated that N stress sensitivity and plant functioning under N-limited conditions may not be under the same genetic control and that the dwarfing genes may play an important role in the tolerance to N stress.
Meeting of the Eucarpia Cereal Section, 2006/11/13-17, Lleida (Spain)